Impact of automation technology on gender parity in maritime industry - Kim, Tae-eun; Sharma, Amit; Gausdal, Anne Haugen; Chae, Chong-ju (WMU journal of maritime affairs, 2019)
Autonomous technological advancement is projected to be a major step change in the world of shipping, creating new opportunities and challenges for maritime authorities and all stakeholders in the maritime sector. In this paper, we aim to explore the influence of automation technology implementation on employment opportunities for women seafarers/operators in the merchant shipping industry. A group of subject matter experts, which composed of shipowners, maritime education and training providers, and shipboard officers, were invited to elaborate on the perceived barriers and the prospects of female employment in the era of autonomous shipping, through a qualitative exploration. The collected data was analysed using thematic analysis to identify the potential challenges, barriers and opportunities for women employment in the maritime industry. The findings from this study reveal measures to improve gender parity in the maritime industry and help address the strategic directions of the International Maritime Organization (IMO) on women empowerment and the Sustainable Development Goal 5 (SDG 5) of the United Nations.